Zgoda wyrażona przez osoby opiekujące się osobą starszą na jej udział w postępowaniu diagnostyczno-terapeutycznym - wybrane zagadnienia prawne - Augustynowicz, Anna; Wrześniewska-Wal, Iwona; Czerw, Aleksandra (Journal of Education, Health and Sport, 2015)
Augustynowicz Anna, Wrześniewska-Wal Iwona, Czerw Aleksandra. Zgoda wyrażona przez osoby opiekujące się osobą starszą na jej udział w postępowaniu diagnostyczno-terapeutycznym - wybrane zagadnienia prawne = The consent by those caring for an older person participating in the investigation diagnostic and therapeutic - selected legal issues. Journal of Education, Health and Sport. 2015;5(6):73-78. ISSN 2391-8306. DOI 10.5281/zenodo.18300 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A73-78 https://pbn.nauka.gov.pl/works/563316 http://dx.doi.org/10.5281/zenodo.18300 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.04.2015. Revised 28.05.2015. Accepted: 04.06.2015. Zgoda wyrażona przez osoby opiekujące się osobą starszą na jej udział w postępowaniu diagnostyczno-terapeutycznym - wybrane zagadnienia prawne The consent by those caring for an older person participating in the investigation diagnostic and therapeutic - selected legal issues Anna Augustynowicz1, Iwona Wrześniewska-Wal2, Aleksandra Czerw3 1Zakład Ekonomiki, Prawa i Zarządzania, Szkoła Zdrowia Publicznego Centrum Medyczne Kształcenia Podyplomowego w Warszawie, Zakład Zdrowia Publicznego Warszawskiego Uniwersytetu Medycznego 2Zakład Ekonomiki, Prawa i Zarządzania, Szkoła Zdrowia Publicznego Centrum Medyczne Kształcenia Podyplomowego w Warszawie 3Zakład Zdrowia Publicznego Warszawskiego Uniwersytetu Medycznego Adres do korespondencji: Centrum Medyczne Kształcenia Podyplomowego 01 - 826 Warszawa; ul. Kleczewska 61/63; tel. 22 56-01-140 Streszczenie: Zgoda na wykonanie zabiegu medycznego jest podstawą legalności czynności medycznych. Dotyczy to zarówno zabiegów wysokiego ryzyka, jak i badań rutynowych. Obowiązujące przepisy prawne przyznają pacjentowi autonomię, co oznacza prawo do wyrażenia zgody na udzielenie określonych świadczeń zdrowotnych lub ich odmowy. W celu podjęcia prawidłowej decyzji pacjent musi być poinformowany o stanie swojego zdrowia, rozpoznaniu, proponowanych oraz możliwych metodach diagnostycznych, leczniczych, dających się przewidzieć następstwach ich zastosowania albo zaniechania, wynikach leczenia oraz rokowaniu. Podmiotem uprawnionym do wyrażenia zgody jest osoba, która ukończyła 18 lat i zachowuje zdolność świadomego wyrażania woli oraz nie jest całkowicie ubezwłasnowolniona. Jeśli pacjent nie spełnia kryteriów wyżej wskazanych, niezbędna jest zgoda zastępcza. W przypadku pacjentów ubezwłasnowolnionych całkowicie lub niezdolnych do świadomego wyrażenia zgody, osobą uprawnioną do wyrażenia zgody jest przedstawiciel ustawowy. W razie braku przedstawiciela ustawowego zgodę na badanie może wyrazić opiekun faktyczny. Przez badanie należy rozumieć podstawowe czynności lekarza polegające na oględzinach ciała i badaniu fizykalnym. Jeśli pacjent nie ma przedstawiciela ustawowego lub gdy porozumienie z nim nie jest możliwe niezbędne jest zezwolenie sądu opiekuńczego. W sytuacjach nadzwyczajnych o zasadności udzielenia świadczenia zdrowotnego decyduje lekarz po konsultacji, w miarę możliwości, z innym lekarzem. Chodzi tu o sytuację, gdy pacjent wymaga niezwłocznej pomocy lekarskiej, a ze względu na stan zdrowia lub wiek nie może zgody wyrazić i nie ma możliwości porozumienia się z jego przedstawicielem ustawowym. Podobnie, gdy udzielenie świadczenia zdrowotnego jest niezbędne do usunięcia niebezpieczeństwa utraty życia, ciężkiego uszkodzenia ciała lub ciężkiego rozstroju zdrowia. Summary: Consent to execute a medical procedure is the basis of the legality of medical procedures. This applies to both high-risk procedures as well as routine testing. The current legislation admit a patient autonomy, which means the right to consent to the granting health benefits or their refusal. In order to make the correct decision, patients must be informed about a medical condition, diagnosis, proposed and possible methods of diagnosis, treatment, foreseeable consequences of their application or omissions, the results of treatment and prognosis. The entity authorized to consent is a person who is 18 years old and retains the ability to consciously express the will and is not completely incapacitated. If you do not meet the criteria indicated above, it is necessary to consent replacement. For patients completely incapacitated or incapable of informed consent, the person entitled to consent is a legal representative. In the absence of a legal representative agreed to study the actual caregiver can express. For a study to be a doctor to understand the basic operations involving the examination of the body and physical examination. If the patient does not have a legal representative or when the agreement with him is not possible it is necessary to permit the Court of Protection. In emergencies, the merits of granting health services prescribed by a doctor after consultation, where possible, with another doctor. It is a situation when a patient requires immediate medical attention, and because of health or age can not consent expressed and it is not possible to communicate with his legal representative. Similarly, where the provision of health services is essential to remove the danger of loss of life, serious injury or serious health disorder. Słowa kluczowe: osoba starsza, zgoda, sąd opiekuńczy, przedstawiciel ustawowy. Key words: an older person, consent, the Court of Protection, the legal representative.